2011
DOI: 10.1002/anie.201103316
|View full text |Cite
|
Sign up to set email alerts
|

Double Single‐Crystal‐to‐Single‐Crystal Transformation and Small‐Molecule Activation in Rhodium NHC Complexes

Olena V. Zenkina,
Eric C. Keske,
Ruiyao Wang
et al.

Abstract: Three gases, one crystal: rhodium NHC complexes undergo back-to-back single-crystal-to-single-crystal transformations by selective nonreversible ligand exchange reactions. Slow diffusion of O(2) converts a dinitrogen complex into a dioxygen complex, and CO subsequently replaces O(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 95 publications
1
50
0
Order By: Relevance
“…Crystal size also probably affects reaction time in SC−SC transitions because of surface area to volume ratio implications. Molecular designs that enable such transitions to take place involve use of bulky ligands or anions which dominate the packing and thus can create a rigid, porous, structure in which smaller movements around the metal centre are made possible [ 13 , 70 ]. SC−SC reactions present excellent possibilities for selectivity to be controlled within a solid-state environment, as the reaction cavity necessarily must remain well defined throughout to preserve crystallinity.…”
Section: Single-crystal-to-single-crystal Transformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal size also probably affects reaction time in SC−SC transitions because of surface area to volume ratio implications. Molecular designs that enable such transitions to take place involve use of bulky ligands or anions which dominate the packing and thus can create a rigid, porous, structure in which smaller movements around the metal centre are made possible [ 13 , 70 ]. SC−SC reactions present excellent possibilities for selectivity to be controlled within a solid-state environment, as the reaction cavity necessarily must remain well defined throughout to preserve crystallinity.…”
Section: Single-crystal-to-single-crystal Transformationsmentioning
confidence: 99%
“…SC−SC transitions may also occur sequentially. In an elegant example, Crudden and co-workers [ 70 ] presented a double SC−SC gas exchange reaction using the (S I Pr) 2 RhCl(L) system , L=N 2 , O 2 or CO; scheme 10 ). First, N 2 is replaced with O 2 to give a dioxygen adduct, and then O 2 is replaced with CO, without crystal degradation at either stage.…”
Section: Single-crystal-to-single-crystal Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the oxazoline substrates are readily accessible from the corresponding carboxylic acids through condensation with 2aminopropan-1-ol. It was found that ac onsistently high yield of 3aa can be obtained using acatalyst generated by preheating (60 8 8C, 1h)amixture of [RhCl(C 2 H 4 ) 2 ] 2 and L6.F AB-MS and 13 CNMR analysis of the preheated solution of [RhCl(C 2 H 4 ) 2 ] 2 and L6 suggested exclusive generation of the bis-NHC species [13] [(L6) 2 RhCl + : 802.3420; 13 With the method to generate an active catalyst in hand, we next examined the scope of the C À H/C À Oc ross-coupling with respect to the aryl carbamate component. [11,12] Interestingly,t he use of [RhCl(C 2 H 4 ) 2 ] 2 instead of [RhCl(cod)] 2 as the catalyst precursor along with L6 considerably improved the yield of 3aa,a lthough the yields were variable between experiments (Scheme 2).…”
mentioning
confidence: 99%
“…[11,12] Interestingly,t he use of [RhCl(C 2 H 4 ) 2 ] 2 instead of [RhCl(cod)] 2 as the catalyst precursor along with L6 considerably improved the yield of 3aa,a lthough the yields were variable between experiments (Scheme 2). It was found that ac onsistently high yield of 3aa can be obtained using acatalyst generated by preheating (60 8 8C, 1h)amixture of [RhCl(C 2 H 4 ) 2 ] 2 and L6.F AB-MS and 13 CNMR analysis of the preheated solution of [RhCl(C 2 H 4 ) 2 ] 2 and L6 suggested exclusive generation of the bis-NHC species [13] [(L6) 2 RhCl + : 802.3420; 13 With the method to generate an active catalyst in hand, we next examined the scope of the C À H/C À Oc ross-coupling with respect to the aryl carbamate component. As shown in Scheme 3, this transformation is applicable to aryl carbamates bearing arange of functional groups,including ketones (3ab), nitriles (3ad), fluorides (3ac and 3ae), and amides (3ak).…”
mentioning
confidence: 99%